Augmenting the double pipe heat exchanger efficiency using varied molar Ag ornamented graphene oxide (GO) nanoparticles aqueous hybrid nanofluids - Armstrong, Michael; Mahadevan, Sivasubramanian; Selvapalam, Narayanan; Santulli, Carlo; Palanisamy, Sivasubramanian; Fragassa, Cristiano (Frontiers in Materials, 2023)
The optimization of heat transfer in heat exchanging equipment is paramount for the efficient management of energy resources in both industrial and residential settings. In pursuit of this goal, this empirical study embarked on enhancing the heat transfer performance of a double pipe heat exchanger (DPHX) by introducing silver (Ag)-graphene oxide (GO) hybrid nanofluids into the annulus of the heat exchanger. To achieve this, three distinct molar concentrations of Ag ornamented GO hybrid nanoparticles were synthesized by blending GO nanoparticles with silver nitrate at molarities of 0.03 M, 0.06 M, and 0.09 M. These Ag-GO hybrid nanoparticles were then dispersed in the base fluid, resulting in the formation of three distinct hybrid nanofluids, each with a consistent weight percentage of 0.05 wt%. Thorough characterization and evaluation of thermophysical properties were performed on the resulting hybrid nanomaterials and nanofluids, respectively. Remarkably, the most significant enhancement in heat transfer coefficient, Nusselt number, and thermal performance index (62.9%, 33.55%, and 1.29, respectively) was observed with the 0.09 M Ag-GO hybrid nanofluid, operating at a Reynolds number of 1,451 and a flow rate of 47 g/s. These findings highlight the substantial improvement in thermophysical properties of the base fluid and the intensification of heat transfer in the DPHX with increasing Ag molarity over GO. In summary, this study emphasizes the vital importance of optimizing the molarity of the material, which also plays a significant role in nanoparticle synthesis to achieve the optimal amplification of heat transfer.